1997
DOI: 10.1093/ageing/26.3.189
|View full text |Cite
|
Sign up to set email alerts
|

Fear of falling and restriction of mobility in elderly fallers

Abstract: The study indicated that about one-third of elderly people develop a fear of falling after an incident fall and this issue should be specifically addressed in any rehabilitation programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
448
1
36

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 754 publications
(504 citation statements)
references
References 13 publications
19
448
1
36
Order By: Relevance
“…It was also observed that there is a significant moderate correlation between the FES-I-BRAZIL scale and the variables TUG, FRT, and HF. Vellas et al 27 Lopes KT, Costa DF, Santos LF, Castro DP, Bastone AC that a mobility deficit caused by fear of falling indicates that this fear has been manifesting itself for a longer period of time to the point that it hampers mobility. It is also known that 15 to 20% of older adults who are afraid of falling have a mobility deficit 28 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also observed that there is a significant moderate correlation between the FES-I-BRAZIL scale and the variables TUG, FRT, and HF. Vellas et al 27 Lopes KT, Costa DF, Santos LF, Castro DP, Bastone AC that a mobility deficit caused by fear of falling indicates that this fear has been manifesting itself for a longer period of time to the point that it hampers mobility. It is also known that 15 to 20% of older adults who are afraid of falling have a mobility deficit 28 .…”
Section: Discussionmentioning
confidence: 99%
“…These are all strategies to reduce the risk of falls. Restrictions to mobility will result in a loss of physical conditioning, muscle atrophy, balance deficit and dependence to execute ADLs 21,27,29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although falls often have a multi factorial etiology, most falls occur while walking 8) , and it is not surprising that gait impairment is also associated with increased risk of falls 9,10) . Gait dysfunction is a factor that makes daily living activities difficult and is a cause of serious functional disorders 11) . Furthermore, subjects who fall can develop a fear of falling, which may limit their physical and social activities, and lead to reduced mobility, physical fitness, thereby increasing the risk of falling 12) .…”
Section: Introductionmentioning
confidence: 99%
“…4 In addition to the obvious physical burden, the physiologic consequence of falling has been associated with significant loss of independence and decreased quality of life. 5 The prevention of falls is, therefore, important to reduce morbidity and mortality in people with diabetes.…”
mentioning
confidence: 99%